HUBUNGAN ANTARA PANJANG TUNGKAI TERHADAP HASIL LARI 100 METER ATLET ATLETIK MAHASISWA UNIVERSITAS MUHAMMADIYAH SORONG - Ade Mawang Kililaw; Agus Kurniadi; Istiyono (STKIP Subang, 2026)
This study aims to analyze the relationship between leg length and the results of running 100 meters in athletic athletes of the University of Muhammadiyah Sorong. The study used a quantitative approach with a correlational design to determine the level of relationship between anthropometric variables and sprint performance. The research sample amounted to 30 student athletes who were selected through purposive sampling techniques with the criteria of active students, registered as members of the Athletic UKM, and in good physical condition at the time of data collection. Leg length was measured using an anthropometer from the superior anterior iliac spina to the sole of the foot, while 100-metre running performance was measured using a digital stopwatch on a standard track, with two trials and best times taken. Data analysis was carried out through descriptive statistics, normality tests, and Pearson Product Moment correlation tests at a significance level of 0.05. The results showed a significant negative relationship between leg length and 100-meter running time (r = -0.62; p < 0.05). The determination coefficient of 0.38 showed that leg length contributed 38% to the variation in the results of the 100-meter run. These findings indicate that the longer the athlete's legs, the greater the potential to produce longer steps that support the achievement of maximum speed. Thus, leg length is one of the factors that contribute to sprint performance, although it is still influenced by other factors such as muscle strength, power, and running technique.